Friction surface phenomena - Shpenkov, Georgii Petrovich (Tribology series, 1995)
This monograph summarises results of research in some surface phenomena, observed in mechanical treatment and friction. In particular the book is devoted to urgent problems of the science of friction and wear and provides insight into the mechanism of the phenomena that cause, on the one hand, anomalously low coefficients of friction and wear (the so-called selective transfer) and on the other, dramatic damages of the surface layers during sliding (hydrogen wear of metals). The nature of metal interaction during sliding in selective transfer and hydrogen wear modes is analysed in detail. Furthermore results of studies concerned with certain aspects of phenomena appearing in the process of influencing contacting surfaces and with detecting the relationship between the observed characteristics and behavior of investigated materials in the process of mechanical treatment and friction are presented. The principle followed is to combine varied experimental facts, physical concepts and investigation methods, which at first sight appear to be unrelated, and using this approach to determine general rules. Chapter one provides the reader with a general understanding of fundamental surface phenomena which provide the background to their dynamic interaction in mechanical treatment and under friction. Chapter two deals with the laws governing influence of mechanical effects on the surface. The third chapter presents the fundamentals of the selective transfer theory under friction. Other chapters deal with the possibilities of the Mssbauer electron spectroscopy method, widely used in physics for solving tribology problems, the influence of external electromotive force sources on contact resistance and friction pairs' wear, and hydrogen wear of metals under friction.